Production of indole antibiotics induced by exogenous gene derived from sponge metagenomes1. Issue 5 (21st May 2015) - Takeshige, Yuya; Egami, Yoko; Wakimoto, Toshiyuki; Abe, Ikuro
<x xml:space="preserve">Abstract</x> Sponge metagenomes are accessible genetic sources containing genes and gene clusters responsible for the biosynthesis of sponge-derived bioactive natural products.